The Effect of Educational Background, Work Ethic, Leadership, and Work Motivation on the Performance of Balakada Pusziad Personnel in Supporting the Construction of the Outer Island Territorial Unit of Rote NDAO - M. Syahairony; Guntur Saputro; Suwito Suwito (Journal of Social Research, 2026)
Personnel performance is a strategic factor in supporting the effective implementation of military organizational duties, especially in Balakada Pusziad as a technical implementing element under the Army Zeni Center, which is responsible for supporting engineering equipment and construction to enhance the unit’s operational readiness. The increasing complexity of tasks and demands for professionalism require performance optimization through the strengthening of internal organizational factors. This study aims to analyze the influence of educational background, work ethic, leadership, and work motivation on the performance of Balakada Pusziad personnel. The research uses a quantitative approach with survey methods and a saturated sampling technique. Data were collected through questionnaires that had been tested for validity and reliability, then analyzed using descriptive statistics, classical assumption tests, multiple linear regression, and SWOT analysis with the help of SPSS. The results of the study show that educational background, work ethic, leadership, and work motivation, partially or simultaneously, have a positive and significant effect on personnel performance. The discussion indicates that work motivation strengthens the influence of independent variables in improving performance outcomes. It was concluded that the improvement of the performance of Balakada Pusziad personnel is determined by the synergy among the quality of education, the strengthening of work ethic, leadership effectiveness, and the optimization of work motivation as internal driving factors of the organization.